Governing agriculture-forest landscapes to achieve climate change mitigation - Agrawal, A.; Wollenberg, Eva Karoline; Persha, L. (Elsevier, 2014)
This introduction to the special section on “Governing Agriculture-Forest Landscapes to Achieve Climate Change Mitigation” reviews external interventions to improve forest conditions and reduce deforestation, and by extension, influence carbon storage in agriculture-forest landscapes. The review is based on a careful survey of 123 cases of project-based and policy interventions to influence land use and forest cover outcomes. We propose that outcomes of interventions can be explained in terms of rights, incentives, and technologies related to land use and apply this framework to examine 12 types of interventions in agriculture-forest landscapes. The analysis of the identified 123 cases raises concerns about consistency of data and comparability of cases. Our preliminary evidence suggests limited association between the stated objective of an intervention and its success. This evidence also suggests that smaller scale and effective enforcement may be positively associated with improved forest outcomes. But the effectiveness of interventions across different agriculture-forest landscapes varies and available evidence does not permit easy generalizations. The variable effects of interventions across different agriculture-forest landscapes point to the need to better understand the forms and functions of interventions and to problems associated with assessing their relative efficacy.